Study on the User Segmentation Method Based on the Combination of User-FRT Matrix and HAC in the View of the Product Usage Scenarios - Hang Liu, Jiahuan Li, Zan Ren (Forest Chemicals Review, 2022)
The importance of user need is widely known in product design stage. However, how to build up a clear correspondence between a certain type of user and a product function is still an issue. In order to solve this problem, this paper proposes a user segmentation method based on product usage scenarios. By clustering the usage situation of product function modules, product usage scenarios that meet different user demand levels can be obtained and the user segmentation is thereby achieved. In this paper, the Kano model is first applied to determine customers’ functional requirements to construct the User-FRT matrix and acquire the functional performance index. The R-type clustering is then used to cluster the numerous functional performance indexes in order to reduce the amount of computation. Finally, the user segmentation is achieved by using hierarchical agglomerative clustering method in accordance with the simplified indicators. A case study of agricultural UAVs is implemented to verify the proposed method.